Using Mobile-based Social Media to Facilitate Interaction and Build Communities through the lens of Ubuntu in Distance Education - Mpine Makoe (Commonwealth of Learning, 2019)
This paper examines how WhatsApp can be used to build learning communities and facilitate interaction, through the lens of Ubuntu – an African concept of humanness, which means that an individual person owes his or her existence to the existence of others. The Afrocentric concept of Ubuntu and interaction work concomitantly towards the realisation of vocabulary teaching and learning within distance education. Through this study, students were encouraged to work together through a mobile-based social network to learn English vocabulary. Ubuntu was used as a framework to analyse the WhatsApp chats to find salient themes relating to building communities and enhancing interaction. The key elements of Ubuntu grounded the findings and demonstrated how technology can be used to bridge the interaction distance and how Ubuntu principles are articulated in the communities of learning. This paper illustrates how Ubuntu is manifested in a local context, with principles that can be applied globally to enhance collaboration.